Inspirasi alam dalam karya seni Seramik di Malaysia - Nami, Ak. Go. (Universiti Malaysia Sarawak, (UNIMAS), 2007)
Employing the elements ofnature into the artworks seem to be synonymous in the visual art scene in Malaysia. Many artist with their various approaches had tried to convey their message through to the audience, and ceramics is among one ofthem. The fondness in manipulating these elementji-om our beautifit! nature has greatly inspired the artist in the creation ofthe body ofher clay images.